Are there Sex Differences in Confidence and Metacognitive Monitoring Accuracy for Everyday, Academic, and Psychometrically Measured Spatial Ability? - Ariel, Robert (Intelligence, 2018)
The current study evaluated sex differences in (1) self-perceptions of everyday and academic spatial ability, and (2) metacognitive monitoring accuracy for measures of spatial visualization and spatial orientation. Undergraduate students completed the Paper Folding Test, Spatial Relations Test, and the Revised Purdue Spatial Visualization Test while making confidence judgments (CJs) for each trial. They also made global estimates of performance and rated their ability to perform several everyday and academic spatial scenarios. Across multiple spatial measures, female students displayed lower confidence in their item-level monitoring and global assessments of performance than did male students, even when no actual differences in spatial performance occurred. Women were also less confident in their self-assessments of their visualspatial ability for scientific domains than were men. However, the absolute and relative accuracy of CJs did not differ as a function of sex suggesting that women can monitor their spatial performance as well as men.